Analisis pengaruh faktor-faktor fundamental terhadap harga saham pada perusahaan manufaktur di Bursa Efek Indonesia (BEI) - Wijaya, Dermawan (Universitas Tarumanagara, 2017)
This research aims to analyze the effect of fundamental factors on stock prices in manufacturing companies that are listed on the Indonesia Stock Exchange. Fundamental factors that become this research object are current ratio (CR), debt to equity (DER), return to equity ratio (ROE), total assets turnover (TATO), and earning per share (EPS) as independent variables, while stock price becomes dependent variables. The research subject is manufacturing companies listed in the Indonesia Stock Exchange between the period 2013-2016 and have published profitable financial statements. The sampling method used is purposive sampling and the analysis method used is panel data regression. The research model selected is fixed effect model (FEM). The result shows that CR, DER, ROE, TATO, and EPS have significant and simultaneous effects on stock price. Where only ROE and EPS have a significant and partial effect on the stock price. This study concludes that not all independent variables have a significant effect on stock price.